Olive Leaf Extract Attenuates Inflammatory Activation and DNA Damage in Human Arterial Endothelial Cells - Burja, Blaž; Kuret, Tadeja; Janko, Tea; Topalović, Dijana; Živković, Lada; Mrak-Poljšak, Katjuša; Spremo-Potparević, Biljana; Žigon, Polona; Distler, Oliver; Čučnik, Saša; Sodin-Semrl, Snezna; Lakota, Katja; et al. (Frontiers in Cardiovascular Medicine, 2019)
Olive leaf extract (OLE) is used in traditional medicine as a food supplement and as an over-the-counter drug for a variety of its effects, including anti-inflammatory and anti-atherosclerotic ones. Mechanisms through which OLE could modulate these pathways in human vasculature remain largely unknown. Serum amyloid A (SAA) plays a causal role in atherosclerosis and cardiovascular diseases and induces pro-inflammatory and pro-adhesive responses in human coronary artery endothelial cells (HCAEC). Within this study we explored whether OLE can attenuate SAA-driven responses in HCAEC. HCAEC were treated with SAA (1000nM) and/or OLE (0.5 and 1mg/ml). The expression of adhesion molecules VCAM-1 and E-selectin, matrix metalloproteinases (MMP2 and MMP9) and miRs 146a, let-7e and let-7g (involved in the regulation of inflammation) was determined by qPCR. The amount of secreted IL-6, IL-8, MIF and GRO-α in cell culture supernatants was quantified by ELISA. Phosphorylation of NF-κB was assessed by Western blot and DNA damage was measured using the COMET assay. OLE decreased significantly released protein levels of IL-6 and IL-8, as well as mRNA expression of E-selectin in SAA-stimulated HCAEC and reduced MMP2 levels in unstimulated cells. Phosphorylation of NF-κB (p65) was upregulated in the presence of SAA, with OLE significantly attenuating this SAA-induced effect. OLE stabilized SAA-induced upregulation of microRNA-146a and let-7e in HCAEC, suggesting that OLE could fine-tune the SAA-driven activity of NF-κB by changing the microRNA networks in HCAEC. SAA induced DNA damage and worsened the oxidative DNA damage in HCAEC, whereas OLE protected HCAEC from SAA- and H2O2-driven DNA damage. OLE significantly attenuated certain pro-inflammatory and pro-adhesive responses and decreased DNA damage in HCAEC upon stimulation with SAA. The reversal of SAA-driven endothelial activation by OLE might contribute to its anti-inflammatory and anti-atherogenic effects in HCAEC.